(untitled) (Private Law, 2025)
The development of technology in today’s society has also given rise to new innovations in financial services based on information technology known as Financial Technology (Fintech). Fintech lending or also called Fintech Peer-to-Peer Lending or services. borrowing and lending money based on information technology is one of the innovations in the financial sector by utilizing technology that allows lenders and borrowers to carry out borrowing and lending transactions without having to meet in person. The borrowing and lending transaction mechanism is carried out through a system that has been provided by the Fintech Lending organizer, either through an application or a website. This study uses qualitative research through library research that will examine the principles of debt according to the hadith and the version of loan debt. Therefore, online loans that are in accordance with the practice of the Prophet Muhammad saw. are the absence of additional money or nominal from the creditor (owner of the money), because if that happens then the interpretation is different, then that is what is called usury. However, seen from the practice of online loans that are circulating, the agreement at the beginning is stated with the interest rate already found starting from 3% and so on, so if the online loan is in the form of that, of course it is said to be a loan that contains usury and is not in accordance with the Hadith of the Prophet Muhammad.